BUILDING TOMORROW'S LEADERS TODAY: Strategic Talent-Succession Fusion in Indonesian Provincial Governance - Munawaroh Munawaroh; Aninda Nadya Bilqis; Ely Mustofiyah; Eva Sofianty; Siti Muawanah (Yayasan Education and Social Center, 2026)
This study investigates the strategic integration of talent management and succession planning in human resource management within Banten Provincial Government, Indonesia, specifically examining the Regional Personnel Agency's (BKD) role as the primary architect of civil service workforce development. Employing a qualitative methodology combining desk research and structured observation, this research unveils a critical yet underutilized framework that positions talent identification, development, and succession as interconnected strategic imperatives rather than isolated administrative functions. Findings reveal that while regulatory infrastructure supports integrated talent-succession systems, implementation gaps persist due to inadequate information systems, cultural resistance to merit-based advancement, budget constraints, and political interference in personnel decisions. Key enablers include leadership commitment, comprehensive personnel databases, and supportive regulations. The strategic fusion of these systems significantly enhances organizational performance, employee retention, competency development, and cost efficiency. This research contributes actionable insights for public sector modernization in developing nations navigating the complexities of bureaucratic reform in VUCA environments, offering a replicable model for sustainable leadership development in Indonesian provincial governance.